On the correlation of self-reported and behavioral risk attitude measures: The case of the General Risk Question and the Investment Game following Gneezy and Potters (1997) - Christine Gaertner; Petra Steinorth (Risk Management and Insurance Review, 2023)
Risk attitudes play a pivotal role to understand economic decision-making, and several measures are used to elicit them in the lab and survey them in the field. We provide a literature review on the most commonly used risk elicitation methods by Holt and Laury (HL) and the Investment Game (IG) by Gneezy and Potters and the General Risk Question (GRQ) utilized in the German Socioeconomic Panel. Based on the metadata from three experiments, we show that the GRQ has a robust and economically relevant association with the IG.
Keywords: 330